Efficacy of febuxostat on hyperuricemia and estimated glomerular filtration rate in patients with non-dialysis stage 3/4 chronic kidney disease and assessment of cardiac function: a 12-month interventional study - Waheed, Yousuf Abdulkarim; Yang, Fan; Liu, Jie; Almayahe, Shifaa; Selvam, Karthick Kumaran Munisamy; Wang, Disheng; Sun, Dong (Frontiers in Nephrology, 2025)
ObjectivesFebuxostat, an oral medication for treating hyperuricemia (HUA), is a non-purine xanthine oxidase inhibitor that regulates serum uric acid (SUA) metabolism in patients with chronic kidney disease (CKD). However, the drug’s effectiveness in improving renal function in patients with non-dialysis stage 3/4 CKD remains unclear. Our aim is to investigate the efficacy of febuxostat on kidney function. In addition, the cardiac function will be assessed.MethodWe conducted a single-center, interventional, randomized, controlled, open-label study. A total of 316 patients with non-dialysis stage 3/4 CKD, with SUA ≥6mg/dL in women and ≥7mg/dL in men, were assigned to either the febuxostat group (n=156) or the control group (n=160). The primary endpoint was the evaluation of changes in kidney biomarkers from baseline to 12 months of treatment, and any changes in cardiac biomarkers and echocardiographs were the secondary endpoint.ResultsThe primary endpoint was a comparison between the two groups from baseline to 12 months of treatment. SUA was significantly decreased in patients treated with febuxostat 40 mg (6.85 ± 0.41mg/dL at baseline and 5.27 ± 0.70mg/dL at 12 months of treatment, P<0.001) and this was associated with increased eGFR (34.48 ± 8.42ml/min at baseline and 38.46 ± 8.87ml/min at 12 months of treatment, P<0.001). There were significant decreases in high-sensitivity troponin T (19.50 ± 7.24ng/L at baseline and 16.98 ± 7.32ng/L at 12 months of treatment, P<0.001) and N-terminal-pro brain natriuretic peptide (941.35 ± 374.30pg/ml at baseline and 762.22 ± 303.32 pg/ml at 12 months of treatment, P<0.001) in the febuxostat group. These changes were also associated with increased left ventricular ejection fraction in the febuxostat group (50.47 ± 3.95% at baseline and 51.12 ± 3.96% at the end of the study, P<0.001).ConclusionIn the interventional group, febuxostat was well-tolerated and demonstrated a reduction in SUA associated with an increase in eGFR. This slowed down the progression of renal disease in patients with non-dialysis stage 3/4 CKD and improved cardiac function.